Where in the world is the Philippines? debating its national territory - Severino, Rodolfo (Institute of Southeast Asian Studies, 2010)
" 'Where in the world is the Philippines?' is a question that has been deftly and consistently dodged by our politicians at the expense of clearly defining the Philippines' territorial and maritime jurisdictions. Severino's scholarly work lays out what has happened in the past and what must be done in the future - and does so just as newly elected President Benigno S. Aquino begins his term in office. With the help of this timely and comprehensive study, it is imperative that Aquino and the Congress confront and resolve territorial issues once and for all." - Roberto R. Romulo, former Secretary of Foreign Affairs of the Philippines.